A Double Case: Socket Shield and Pontic Shield Techniques on Aesthetic Zone - Carlos Polis-Yanes; Carla Cadenas-Sebastián; Claudia Oliver-Puigdomenech; Raul Ayuso-Montero; Antoni Marí-Roig; José López-López (Case Reports in Dentistry)
When a tooth is extracted, a bone remodeling of the alveolar process occurs irretrievably. Various techniques have emerged over time to maintain the thickness of the bone crest in fixed prosthetics on teeth and implants. The socket shield and pontic shield techniques are aimed at minimizing buccal bone remodeling, especially in the aesthetic area. We present a case of an aesthetic sector rehabilitated with partial fixed denture using the socket shield and pontic shield techniques.